Avaliação da autoeficácia materna em amamentar no puerpério imediato - Bárbara Brandão Lopes; Anne Fayma Chaves Lopes; Dharlene Giffoni Soares; Hilana Dayana Dodou; Régia Christina Moura Barbosa Castro; Mônica Oliveira Batista Oriá (Universidade Federal do Ceará, 2017)
Objective: to evaluate the maternal self-efficacy in breastfeeding in the immediate puerperium. Methods: this is a cross-sectional study involving 132 puerperae. A form with sociodemographic and obstetrical data and the Breastfeeding Self-Efficacy Scale - Short Form was applied in the rooming-in maternity ward. Results: the majority of the interviewed women presented high self-efficacy (90.9%) and presented medium (9.1%) selfefficacy in breastfeeding. There was no association between Breastfeeding Self-Efficacy Scale-Short Form scores and sociodemographic and obstetric variables. Conclusion: women presented high self-efficacy in breastfeeding, which points to a favorable expectation towards breastfeeding, and nurse professional are required to provide more effective assistance in breastfeeding support.